2010
DOI: 10.1093/jnci/djq300
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Activation of the α9-Nicotinic Receptor During Tumorigenesis in Human Breast Epithelial Cells

Abstract: The alpha9-nAChR is important for nicotine-induced transformation of normal human breast epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
218
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(236 citation statements)
references
References 59 publications
6
218
0
2
Order By: Relevance
“…Several studies have shown NNK-triggered human breast epithelial cell transformation upon long-term (>1 mo) exposure to a low concentration of NNK (100 p.m.) (37). In addition, we recently showed that nicotine (10 mM) can induce transformation in normal breast epithelial cells (MCF-10A) upon forced expression of a9-nAChR (28). Another important concern is that nAChRs can be induced in response to nicotine, NNN, and NNK exposure, which produces a detrimental feedback effect on receptor-ligand binding signaling.…”
Section: Smoking-induced Cancer Formationmentioning
confidence: 97%
See 4 more Smart Citations
“…Several studies have shown NNK-triggered human breast epithelial cell transformation upon long-term (>1 mo) exposure to a low concentration of NNK (100 p.m.) (37). In addition, we recently showed that nicotine (10 mM) can induce transformation in normal breast epithelial cells (MCF-10A) upon forced expression of a9-nAChR (28). Another important concern is that nAChRs can be induced in response to nicotine, NNN, and NNK exposure, which produces a detrimental feedback effect on receptor-ligand binding signaling.…”
Section: Smoking-induced Cancer Formationmentioning
confidence: 97%
“…Since then, various studies have described nAChRs as key molecules that act as central regulators of a complex network governing growth (5,28), angiogenesis (29), metastasis (7), and apoptosis (30) during carcinogenesis in response to the tumor microenvironment. In addition, nAChRs stimulate intracellular signaling pathways in a cell-typespecific manner.…”
Section: Nachr-mediated Signaling Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations